2005
DOI: 10.1007/s00406-005-0600-z
|View full text |Cite
|
Sign up to set email alerts
|

Atypical depressive syndromes in varying definitions

Abstract: ■ Abstract Background Atypical depression (AD) exhibits distinct patterns of gender, bipolar-II disorder, genetic, and neuro-biological measures. Using prospective data from a community sample, this paper identifies criteria (and correlates) for an AD syndrome that maximizes the association with female sex and bipolar-II. Methods The Zurich cohort study is composed of 591 subjects selected from a population-based cohort of young adults in the canton of Zurich in Switzerland, screened in 1978 and followed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 55 publications
8
78
1
7
Order By: Relevance
“…However, the hierarchical DSM-IV definition of atypical depression has been debated in adults and adolescents. 45,47 In addition, mood reactivity did not play an important part in distinguishing subtypes in one previous LCA study. 20 …”
Section: Subtypes and Correlatesmentioning
confidence: 76%
“…However, the hierarchical DSM-IV definition of atypical depression has been debated in adults and adolescents. 45,47 In addition, mood reactivity did not play an important part in distinguishing subtypes in one previous LCA study. 20 …”
Section: Subtypes and Correlatesmentioning
confidence: 76%
“…The cross-sectional symptoms to study should be the symptoms showing the highest prevalence difference between BP-II and MDD depression. Atypical depression symptoms and the hypomanic symptoms of mixed depression were more common in BP-II depression than in MDD depression [21, 37, 48,88,89,90,91]. Finding a bimodal distribution of these symptoms would support a categorical distinction between BP-II and MDD.…”
Section: Resultsmentioning
confidence: 99%
“…First-degree relatives of BP probands had more BP [11], age at onset was lower in BP [57, 105, 106], females were as common as males in BP-I and more common than males in MDD [21, 57, 105, 106], BP-I depression was more atypical and retarded, MDD depression was more sleepless and agitated [19, 21, 57], BP had more recurrences [17, 21, 23], and a strong diagnostic stability [12, 13] not shown by MDD [99, 100]. Regarding BP-II depression, it was more atypical, mixed, and agitated than MDD [54, 88, 90, 91,105,106,107], but not always [108, 109]. …”
Section: Resultsmentioning
confidence: 99%
“…They concluded that their findings did not support the use of a hierarchical ranking of mood reactivity to diagnose atypical depression. They expanded upon this impression in a more recent analysis (Angst et al, 2006) and concluded that the diagnosis of atypical depression could be made with equal utility if either three of five criteria (including mood reactivity) or two of four criteria (excluding mood reactivity) were used.…”
Section: Validity Of Dsm-iv Atypical Depressionmentioning
confidence: 99%